PROBIOTICS FOR INFANTILE COLIC : A SYSTEMATIC REVIEW - Ratu Alicia, Dea Nabila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Colic in infants is a self-limiting ailment; nonetheless, it can be unpleasant for parents and tough for doctors to treat. Approximately 20% of infants suffer from infantile colic, which typically reaches its peak between 5 and 6 weeks of age. The challenge for the medical staff is in making an accurate diagnosis and coming up with a treatment plan for the ailment. In order to give doctors with a full grasp of the problem, current advancements, and future possibilities, the purpose of this review article is to outline the pathophysiology of infantile colic, as well as the treatment choices and prognosis for the condition. There are a few potential treatments for infantile colic, the most prominent of which is the use of probiotics, specifically lactobacillus. The most compelling evidence in support of probiotics comes from the prevention or treatment of these five conditions: necrotizing enterocolitis, acute infectious diarrhea, acute respiratory tract infections, antibiotic-associated diarrhea, and newborn colic. Inhibition of bacterial adhesion, improvement of mucosal barrier function, manipulation of both the innate and adaptive immune systems, release of bioactive metabolites, and control of the enteric and central nervous systems are some of the mechanisms of action that probiotics exhibit.